The Effect of Bangun-Bangun Leaf Soup on Breast Milk Production of Postpartum Mothers in Sidoharjo I Village, Pasar Miring, Pagar Merbau District in 2025 - Jayanti Rida Lestari; Astri Ulina Saragih; Suci Nur Azijah (International Journal of Health and Pharmaceutical (IJHP), 2026)
Breast milk is the primary source of nutrition for newborns and provides long-term benefits for the child's growth and immune system. However, not all postpartum mothers are able to produce sufficient amounts of breast milk. One natural alternative to support and enhance milk production is through the use of herbal plants, one of which is Coleus amboinicus Lour, commonly known as bangun-bangun leaves. This study aims to determine the effect of consuming soup made from bangun-bangun leaves on breast milk production among postpartum mothers. The type of research used is quantitative with a quasi-experimental method and a two-group pre-test post-test control group design. The research was conducted in Desa Sidoharjo I Pasar Miring, Pagar Merbau Subdistrict, Deli Serdang Regency, North Sumatra. The sample consisted of 12 postpartum mothers selected through total sampling. The intervention included administering bangun-bangun leaf soup twice a day for seven days. Data were collected through direct observation and measurement of breast milk volume before and after the intervention. The univariate analysis showed an increase in the number of mothers with smooth milk production after the intervention. The bivariate analysis using the Wilcoxon test revealed a significance value of p = 0.000 (p < 0.05), indicating a significant effect of bangun-bangun leaf soup on milk production. The study concludes that soup made from bangun-bangun leaves is effective in increasing breast milk production among postpartum mothers.